2007
DOI: 10.1158/0008-5472.can-06-2996
|View full text |Cite
|
Sign up to set email alerts
|

In vivoEffects of Vaccination with Six-Transmembrane Epithelial Antigen of the Prostate: A Candidate Antigen for Treating Prostate Cancer

Abstract: Immunotherapy may provide an alternative treatment for cancer patients, especially when tumors overexpress antigens that can be recognized by immune cells. The identification of markers and therapeutic targets that are up-regulated in prostate cancer has been important to design new potential treatments for prostate cancer. Among them, the recently identified six-transmembrane epithelial antigen of the prostate (STEAP) is considered attractive due to its overexpression in human prostate cancer tissues. Our stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 45 publications
4
98
2
Order By: Relevance
“…C57BL/6 mice were purchased from Jackson Laboratory (Bar Harbor, ME). 1: 27-35, AAGIGILTV; 22 gp100: 154-162, KTWGQYWQV; 23 gp100: 209-217, ITDQVPFSV; 24 ovalbumin (OVA): 256-264, SIIN-FEKL, 25 and mouse six-transmembrane epithelial antigen of the prostate (mSTEAP): 326-335, DVSKINRTEM 26 ) in 1 mL of chloroform was emulsified in 6 mL of 2% PVA to form an oil-in-water emulsion. The emulsification was carried out using a micro-tip probe ultrasonic sonicator set at 55 watts of energy output (XL 2015 Sonicator ® ultrasonic processor; Misonix, Inc, Farmingdale, NY) for 2 minutes over an ice bath.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…C57BL/6 mice were purchased from Jackson Laboratory (Bar Harbor, ME). 1: 27-35, AAGIGILTV; 22 gp100: 154-162, KTWGQYWQV; 23 gp100: 209-217, ITDQVPFSV; 24 ovalbumin (OVA): 256-264, SIIN-FEKL, 25 and mouse six-transmembrane epithelial antigen of the prostate (mSTEAP): 326-335, DVSKINRTEM 26 ) in 1 mL of chloroform was emulsified in 6 mL of 2% PVA to form an oil-in-water emulsion. The emulsification was carried out using a micro-tip probe ultrasonic sonicator set at 55 watts of energy output (XL 2015 Sonicator ® ultrasonic processor; Misonix, Inc, Farmingdale, NY) for 2 minutes over an ice bath.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…To investigate whether alloreactivity could either promote or suppress T cell responses against self-Ags against which only lowaffinity T cells would be available, HSCT-transplanted male mice received either an mDLI or an fpDLI and a vaccine composed of male or female DC, respectively, pulsed with a peptide derived from the six-transmembrane epithelial Ag of the prostate (STEAP), found in human and prostate cancer, and previously used in vaccination strategies (37,38). Results depicted in Fig.…”
Section: Dc-based Vaccination Preserves Immunogenicity In the Contextmentioning
confidence: 99%
“…However, this differential efficacy of the cancer vaccine in prophylaxis and therapy has been proven by several other studies evaluating the feasibility of a cancer vaccine with tolerized tumor antigens. [42][43][44][45][46] Novakovic et al 44 found that the proportion of protected mice was 75-100% by vaccination of irradiated melanoma tumor cells with CpG ODN in a prophylactic setting whereas the rates of cured mice were only 11.1-21.1% in a therapeutic setting. Garcia-Hernandez Mde et al 45 recently reported that prophylactic vaccination with a prostate antigen, six-transmembrane epithelial antigen of prostate, significantly delayed tumor growth and improved survival whereas therapeutic vaccination induced a modest delay in the growth of established prostate tumors.…”
Section: Differential Antitumor Effects Of Il-23 H-t Jin Et Almentioning
confidence: 99%
“…[42][43][44][45][46] Novakovic et al 44 found that the proportion of protected mice was 75-100% by vaccination of irradiated melanoma tumor cells with CpG ODN in a prophylactic setting whereas the rates of cured mice were only 11.1-21.1% in a therapeutic setting. Garcia-Hernandez Mde et al 45 recently reported that prophylactic vaccination with a prostate antigen, six-transmembrane epithelial antigen of prostate, significantly delayed tumor growth and improved survival whereas therapeutic vaccination induced a modest delay in the growth of established prostate tumors. Moreover, in a HER-2/neu transgenic mouse model which closely mimics the natural history of human tumors, early vaccination produced a significantly delay in the onset of tumors, whereas late vaccination was completely devoid of an effect in comparison to untreated control mice.…”
Section: Differential Antitumor Effects Of Il-23 H-t Jin Et Almentioning
confidence: 99%